Quality Control for Hospitals' Clinical Ethics Services: Proposed Standards - Leeman, Cavin P. (Cambridge quarterly of healthcare ethics, 1997)
Hospital ethics committees have become widespread over the last 25 years, stimulated by the Quinlan decision of the New Jersey Supreme Court, the report of a President's Commission, and most recently by the Joint Commission on Accreditation of Health Care Organizations (JCAHO), which now man dates that each hospital seeking accreditation have a functioning process for the consideration of ethical issues in patient care. Laws and regulations in several states require that hospitals establish ethics committees, and some states stipulate that certain types of cases and disputes be taken to such committees. At least one state grants legal immunity to those who implement recommendations of an ethics committee.